Role in diuresis of a calcitonin receptor (GPRCAL1) expressed in a distal-proximal gradient in renal organs of the mosquito Aedes aegypti (L.). - Hyeogsun Kwon (Public Library of Science (PLoS), 2012)
Evolution of anthropophilic hematophagy in insects resulted in the coordination of various physiological processes for survival. In female mosquitoes, a large blood meal provides proteins for egg production and as a trade-off, rapid elimination of the excess water and solutes (Na(+), Cl(-)) is critical for maintaining homeostasis and removing excess weight to resume flight and avoid predation. This post-prandial excretion is achieved by the concerted action of multiple hormones. Diuresis and natriuresis elicited by the calcitonin-like diuretic hormone 31 (DH(31)) are believed to be mediated by a yet uncharacterized calcitonin receptor (GPRCAL) in the mosquito Malpighian tubules (MTs), the renal organs. To contribute knowledge on endocrinology of mosquito diuresis we cloned GPRCAL1 from MT cDNA. This receptor is the ortholog of the DH(31) receptor from Drosophila melanogaster that is expressed in principal cells of the fruit fly MT. Immunofluorescence similarly showed AaegGPRCAL1 is present in MT principal cells in A. aegypti, however, exhibiting an overall gradient-like pattern along the tubule novel for a GPCR in insects. Variegated, cell-specific receptor expression revealed a subpopulation of otherwise phenotypically similar principal cells. To investigate the receptor contribution to fluid elimination, RNAi was followed by urine measurement assays. In vitro, MTs from females that underwent AaegGPRcal1 knock-down exhibited up to 57% decrease in the rate of fluid secretion in response to DH(31). Live females treated with AaegGPRcal1 dsRNA exhibited 30% reduction in fluid excreted after a blood meal. The RNAi-induced phenotype demonstrates the critical contribution of this single secretin-like family B GPCR to fluid excretion in invertebrates and highlights its relevance for the blood feeding adaptation. Our results with the mosquito AaegGPRCAL1 imply that the regulatory function of calcitonin-like receptors for ion and fluid transport in renal organs arose early in evolution.